KONSEP PENDIDIKAN ISLAM KRITIS PERSPEKTIF NURCHOLISH MADJID - Vick Ainun Haq (Jurnal Al-Fatih, 2021)
Abstract: The harmony of the principles and goals of Islamic education always leads to every good that is found in new things, but also does not leave results in old traditions. This study aims to describe the concept of Islamic Education from the Perspective of Nurcholish Madjid and the concept of Critical Islamic Education from the Perspective of Nurcholish Madjid. The method in this study uses a qualitative approach with the type of library research. The results of the research show (1) Islamic Education from the perspective of Nurcholish Madjid has the principles and goals of forming an ideal human being. (2) Critical Islamic Education from the Perspective of Nurcholish Madjid, is Democratic-Based Islamic Education and Pluralist-Based Islamic Education Keywords: Islamic Education, Democratic, Pluralist, Nurcholsih Madjid